IMPLEMENTASI MODEL ASESMEN BERBASIS KURIKULUM MERDEKA DI SMK MUHAMMADIYAH KAJEN PEKALONGAN - Safitri, Hani Hasnah (Lembaga Penelitian Dan Pengabdian Masyarakat Stai Brebes, 2024)
This article is presented from the results of research that reveals the achievements of the independent curriculum-based assessment system in improving the quality of learning processes and outcomes at the Muhammadiyah Kajen Pekalongan Vocational High School (SMK). This research uses qualitative research methods with field research, as well as data collection techniques through observation, in-depth interviews, and documentation. The results of this research show that; 1) The independent curriculum-based assessment or assessment system consists of formative assessments, summative assessments, and diagnostic assessments. 2) Kajen Pekalongan Muhammadiyah Vocational School has several forms of assessments based on the independent curriculum. First, the Skills Competency Test (UKK) assessment which measures students' skills at the learning stage. Second, the Field Work Practices (PKL) assessment improves students' professional work culture in the world of work. Third, the ISMUBA (Islam, Muhammadiyah, and Arabic) assessment integrates religion into students' daily lives. All assessment implementations are supported by a conducive learning environment, adequate facilities, and high integrity of educators so that the learning assessment process can run effectively and can improve the quality of students in accordance with the needs of the world of work and society.